A Novel SMAD4 Mutation Causing Severe Juvenile Polyposis Syndrome with Protein Losing Enteropathy, Immunodeficiency, and Hereditary Haemorrhagic Telangiectasia. (1st February 2015) - Johansson, Joel; Sahin, Christofer; Pestoff, Rebecka; Ignatova, Simone; Forsberg, Pia; Edsjö, Anders; Ekstedt, Mattias; Stenmark Askmalm, Marie
Abstract : Juvenile polyposis syndrome (JPS) is a rare genetic disorder characterized by juvenile polyps of the gastrointestinal tract. We present a new pathogenic mutation of the SMAD4 gene and illustrate the need for a multidisciplinary health care approach to facilitate the correct diagnosis. The patient, a 47-year-old Caucasian woman, was diagnosed with anaemia at the age of 12. During the following 30 years, she developed numerous gastrointestinal polyps. The patient underwent several operations, and suffered chronic abdominal pain, malnutrition, and multiple infections. Screening of the SMAD4 gene revealed a novel, disease-causing mutation. In 2012, the patient suffered hypoalbuminemia and a large polyp in the small bowel was found. Gamma globulin was given but the patient responded with fever and influenza-like symptoms and refused more treatment. The patient underwent surgery in 2014 and made an uneventful recovery. At follow-up two months later albumin was 38 g/L and IgG was 6.9 g/L. Accurate diagnosis is essential for medical care. For patients with complex symptomatology, often with rare diseases, this is best provided by multidisciplinary teams including representatives from clinical genetics. Patients with a SMAD4 mutation should be followed up both for JPS and haemorrhagic hereditary telangiectasia and may develop protein loosing enteropathy and immunodeficiency.